Application of Life-Cycle Assessment Approach to Zero Energy Buildings: Case Study of an Office Building in South Korea - Yong Gi Jung; Ji Young Yun; Kang Woo Bae; Se Hyeon Lim; Min Hee Chung; Jin Woo Moon; Jin Chul Park (Advances in Civil Engineering)
This study evaluates the life-cycle carbon footprint of buildings, addressing a key limitation of zero-energy buildings (ZEBs), which primarily focus on operational energy use. This study identified the optimal conditions for structure type and window-to-wall ratio (WWR) of ZEB implementation to evaluate carbon emissions from a life-cycle perspective. Building energy simulations and life-cycle assessment (LCA) analyses were conducted to examine variations in the operational energy consumption and building life-cycle carbon emissions based on different structural materials and WWR configurations. The building selected for this analysis featured a combination of concrete and wood structures, with a WWR of 40% in the north–south direction and 30% in the east–west direction, each increasing by 20%. The findings indicated that increased WWR for both concrete and wood structures increases energy consumption. Moreover, the carbon emissions followed a similar pattern, rising as WWR increases. Regarding life-cycle carbon emissions, the findings suggest transitioning from the current concrete structure to a wood structure while maintaining a low WWR as an effective strategy to achieve carbon neutrality in building operations.